EXPLORING THE CROSS CULTURE UNDERSTANDING IN INDONESIAN EFL CONTEXT: A LITERATURE REVIEW - Aksendro Maximilian; Galuh Dwi Ajeng (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
The objective of the present study is to elaborate some cross-cultural understanding importance for Indonesian EFL students, and the role of EFL teaching in minimizing students’ misunderstanding while using English. This study uses literature review study for collecting the data coming from some sources in the forms of books, and journal articles regarding Cross Culture Understanding in Indonesia. In analyzing the data, the qualitative data from the sources were read, analyzed, classified, and concluded. Based on the result of the study, it is important to teach and provide more cultural content for strengthening the cross culture understanding of the Indonesian students while they are learning English. This study also finds that cross culture understanding materials may give beneficial impact that support the improvement of their English language skills. Moreover, the role of integrating cross cultural understanding content in EFL practice in minimizing the misunderstanding in using English has been proven positively. To sum up, cross-culture understanding in English language teaching in Indonesia should be considered as an important element to be involved in English teaching and learning activity to achieve learning outcomes, and to create Indonesia’s generation to be ready to compete in the era of global competition.